CLONING AND PURIFICATION OF LARGE FRAGMENT OF DNA POLYMERASE I FROM GEOBACILLUS STEAROTHERMOPHILUS AND APPLICATION IN ISOTHERMAL DNA AMPLIFICATION - Li, P.; Amenov , A.; Kalendar , R.; Abeldenov , S.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2017)
The invention of loop-mediated isothermal amplification (LAMP) opened new research avenues in the field in diagnostics. LAMP reactions have important advantages as a diagnostic tool. These advantages include a constant reaction temperature that only requires a simple thermostat instead of a thermocycler and a greater reaction speed from 15 to 30 minutes. The method is based on a specific thermostable polymerase with helicase activity and a set of different primers. We obtained a large fragment of recombinant polymerase I from Geobacillus stearothermophilus expressed in Escherichia coli. Original strain (ATCC 12980) cells were cultivated in nutrient broth to extract genomic DNA and amplify the target gene. After its cloning and expression, the polymerase was purified in an amount of 1.5 mg from 1 L of induction culture of recombinant cells. The purified polymerase was tested and displayed polymerase and helicase activities with no exonuclease activity. These activities were demonstrated in successful LAMP reactions with the amplification of transgenic elements of genetically modified Arabidopsis thaliana using a LAMP primer set for detection of nopaline synthase terminator (T-nos) and another set for detection of the Cauliflower Mosaic Virus 35S promoter. We showed that LAMP reaction products could be detected using an agarose gel and fluorescent dyes.